2015
DOI: 10.1016/j.chroma.2015.11.026
|View full text |Cite
|
Sign up to set email alerts
|

The 3D pore structure and fluid dynamics simulation of macroporous monoliths: High permeability due to alternating channel width

Abstract: Polymethacrylate-based monoliths have excellent flow properties. Flow in the wide channel interconnected with narrow channels is theoretically assumed to account for favorable permeability. Monoliths were cut into 898 slices in 50nm distances and visualized by serial block face scanning electron microscopy (SBEM). A 3D structure was reconstructed and used for the calculation of flow profiles within the monolith and for calculation of pressure drop and permeability by computational fluid dynamics (CFD). The cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…When the liquid is pumped to a convection‐aided chromatography media such as membranes and monoliths, the mobile phase liquid flows through open, highly connected pores that form a network of channels (flow‐through pores) of the media. Friction between a pore wall and the mobile phase liquid results in pressure drop that, as recently demonstrated, can provide not only information about the pore size but also further insight into a monolith structure, including pore connectivity . Since methacrylate monoliths of different pore sizes exhibit similar microstructure and porosity, differences in pressure drop reflect changes in monolith average pore size that determine the surface area and the DBC .…”
Section: Resultsmentioning
confidence: 86%
“…When the liquid is pumped to a convection‐aided chromatography media such as membranes and monoliths, the mobile phase liquid flows through open, highly connected pores that form a network of channels (flow‐through pores) of the media. Friction between a pore wall and the mobile phase liquid results in pressure drop that, as recently demonstrated, can provide not only information about the pore size but also further insight into a monolith structure, including pore connectivity . Since methacrylate monoliths of different pore sizes exhibit similar microstructure and porosity, differences in pressure drop reflect changes in monolith average pore size that determine the surface area and the DBC .…”
Section: Resultsmentioning
confidence: 86%
“…In addition, the work of Jungreuthmayer et al. demonstrated that the flow in monolith showed a lateral velocity component, which may contribute to the transport of molecules to the monolith wall. This confirmed lateral velocity can be speculated to promote the contact between substrate and fixed trypsin.…”
Section: Resultsmentioning
confidence: 99%
“…) is proposed based on computational fluid dynamics (CFD). To obtain reliable results, a detailed microstructure of particular bed has to be obtained, commonly using various imagining techniques . On this base, velocity and pressure drop distribution over the representative bed segment is calculated together with an average values of both.…”
Section: Chromatographic Column Bed Structurementioning
confidence: 99%
“…On this base, velocity and pressure drop distribution over the representative bed segment is calculated together with an average values of both. Stabilized reinforced cellulose membrane as well as silica and methacrylate monolith hydrodynamic properties were recently analyzed using this approach . This methodology can be implemented also on beds with more complex pore structure.…”
Section: Chromatographic Column Bed Structurementioning
confidence: 99%
See 1 more Smart Citation